Antimicrobial Spectrum of Titroleane™: A New Potent Anti-Infective Agent - Bianca Johansen (Antibiotics, 2020)
Tea Tree oil (TTO) is well known for its numerous good properties but might be also irritating or toxic when used topically or ingested, thus limiting the number of possible applications in Humans. The aim of the study was to characterize the antimicrobial spectrum as well as the toxicity of Titroleane™, a new anti-infective agent obtained from TTO but cleared of its toxic monoterpenes part. The susceptibility to Titroleane™ of various pathogens (bacteria and fungi) encountered in animal and human health was studied in comparison with that of TTO. Antimicrobial screening was carried out using the broth microdilution method. Activities against aerobic, anaerobic, fastidious and non-fastidious microorganisms were performed. For all microorganisms tested, the MIC values for Titroleane™ ranged from 0.08% to 2.5%, except for Campylobacter jejuni, and Aspergillus niger. In particular, Titroleane™ showed good efficacy against skin and soft tissue infection pathogens, such as methicillin resistant Staphylococcus aureus (MRSA), intra-abdominal infections and oral pathogens, as well as fish farming pathogens. Toxicity testing showed little and similar cytotoxicities between TTO and Titroleane™ of 37% and 23%, respectively at a concentration of 0.025% (v/v). Finally, we demonstrated that the antimicrobial activity of Titroleane™ is similar to that of TTO.